2021
DOI: 10.1021/acs.macromol.1c02139
|View full text |Cite
|
Sign up to set email alerts
|

Illumination of Conjugated Polymers Reduces the Nucleation Probability and Slows Down the Crystal Growth Rate

Abstract: Using the setup of an optical microscope, we have examined the influence of illumination with white light on the crystallization behavior in molten films of poly(3-(2,5dioctylphenyl)thiophene) and poly(3-hexylthiophene). We observed a reduction in nucleation density and crystal growth rate induced by illumination. The amount of this reduction increased with the increase of light intensity. Melting of samples previously crystallized under illumination and recrystallization of the same samples in the dark showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…P3HT is thought to typically exhibit high nucleation densities, 33,34 which may partly explain the small number of examples in the literature of individual, optically resolvable melt-crystallized morphologies suitable for crystalline growth rate measurements. 20,33,35 Many studies of bulk P3HT crystallization use techniques such as calorimetry and X-ray diffraction, which do not yield nucleation or growth rates. 1,36,37 Using optical microscopy, Koch et al reported ∼60 μm/min growth rate for form I spherulites in a low molecular weight P3HT (below the chain-folding limit of M n ∼ 5.5 kDa) using films with a free surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P3HT is thought to typically exhibit high nucleation densities, 33,34 which may partly explain the small number of examples in the literature of individual, optically resolvable melt-crystallized morphologies suitable for crystalline growth rate measurements. 20,33,35 Many studies of bulk P3HT crystallization use techniques such as calorimetry and X-ray diffraction, which do not yield nucleation or growth rates. 1,36,37 Using optical microscopy, Koch et al reported ∼60 μm/min growth rate for form I spherulites in a low molecular weight P3HT (below the chain-folding limit of M n ∼ 5.5 kDa) using films with a free surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of P3HT, there are very few reports of nucleation and growth rates during melt crystallization. P3HT is thought to typically exhibit high nucleation densities, , which may partly explain the small number of examples in the literature of individual, optically resolvable melt-crystallized morphologies suitable for crystalline growth rate measurements. ,, Many studies of bulk P3HT crystallization use techniques such as calorimetry and X-ray diffraction, which do not yield nucleation or growth rates. ,, Using optical microscopy, Koch et al reported ∼60 μm/min growth rate for form I spherulites in a low molecular weight P3HT (below the chain-folding limit of M n ∼ 5.5 kDa) using films with a free surface. ,, Our group previously observed nucleation and growth of circulites at the air–polymer interface; however, the crystallization at bulk-like temperatures of the remainder of the film resulted in featureless morphology under the optical microscope, so underlayer growth rates could not be extracted and a comparison to surface-induced growth rates could not be established . Furthermore, the bulk-like underlayer was thought to be nucleated by the free surface-induced circulite layer, so it is uncertain whether it corresponded to the same type of morphology that arises during crystallization of bulk P3HT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that light illumination of conjugated polymers can change their physical properties, [ 19 ] microstructure in solution [ 20–22 ] or solid state [ 23 ] as well as mechanical properties of thin films. [ 24,25 ] However, a combination of analysis from theoretical simulation to scalable coating methods relevant for OPVs have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%